#MeToo in Japan - Exploring the #MeToo movement in a patriarchal society - Lyon,Hanna (2020)
The #MeToo movement sparked a massive outrage amongst women in many western countries. Nevertheless, the movement did not gain as much media attention in asian regions. Japan is one of the countries that have generated international dialogue about this phenomena. The purpose of this study is to determine why #MeToo was not as successful in Japan as in many other countries and what the little outcome has led to. Furthermore, it is bringing attention to persistent gender inequalities in an OECD country. The theory applied to this study is theorising patriarchy by Sylvia Walby. By dividing the patriarchy into six structures and seeing #MeToo from a new lens this study breaks down Japanese societal constructs that are very resistant to female empowerment. By using a systematic research overview of previous literature the #MeToo movement in Japan is analysed. Findings show that victims in Japan often keep quiet if they have been sexually violated due to re-victimisation, sexualising of women and group harmony to name a few. Furthermore there are no direct legislations protecting women from sexual harassment in Japan which often leads to blurred lines regarding what is considered sexual assault. This study sparks an interest in why Japan should change legislations and social behaviour to promote gender equality. Lastly, this study provides recommendations on further research and suggests ideas for female empowerment in Japan.
Keywords: #MeToo; Female empowerment; patriarchy; Japan; sexual violence; group harmony; re-victimisation; sexualising women; victim-blaming